Hard-core soft-shell type core-shell structure polymer and concrete and preparation method thereof

By incorporating hard core soft shell core-shell structural polymer into concrete, the balance problem between concrete toughness and strength in the prior art is solved, and the effect of improving concrete toughness while maintaining or improving its strength is achieved.

CN119613629AInactive Publication Date: 2025-03-14RAILWAY CONSTR RES INST OF CHINA ACAD OF RAILWAY SCI CO LTD +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411828877.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art, while adding polymers to improve concrete toughness, often leads to a significant reduction in concrete strength, making it difficult to find a balance between the two.

Method used

Hard-core soft-shell type core-shell structure polymers are used to prepare core-shell particles including rigid cores and flexible shells and incorporate them into concrete to improve the toughness of the concrete while maintaining or increasing the strength of the concrete.

Benefits of technology

While not reducing the strength of the concrete, the toughness of the concrete is significantly improved, achieving a balance between the two.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a hard-core soft-shell type core-shell structure polymer and concrete and a preparation method thereof, and belongs to the technical field of building materials, and the hard-core soft-shell type core-shell structure polymer is prepared from the following raw materials in parts by weight: 200-240 parts of a core monomer pre-emulsion, 160-200 parts of a shell monomer pre-emulsion, 20 parts of an initiator solution and 4.8-6 parts of a functional monomer. The concrete containing the concrete is prepared from the following raw materials in parts by weight: 230 to 275 parts of cement, 135 to 180 parts of mineral admixture, 635 to 705 parts of river sand, 1080 to 1125 parts of gravel, 18 to 50 parts of hard-core and soft-shell type core-shell structure polymer, 4.0 to 6.5 parts of water reducing agent and 130 to 144 parts of water. After the hard-core and soft-shell type core-shell structure polymer is doped into concrete, the toughness of the concrete can be improved, and meanwhile, the strength of the concrete is not reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and more particularly to a hard-core-soft-shell core-shell structure polymer and concrete thereof and a preparation method thereof. Background Art

[0002] Concrete is a brittle material that is prone to brittle failure when subjected to load. Therefore, improving the brittleness of concrete and increasing its toughness are the goals that concrete researchers and engineering technicians strive for. Adding polymers to concrete is one of the effective measures to improve the toughness of concrete. Adding polymers has a good effect on improving the toughness of concrete, but the current disadvantage is that the strength of concrete is significantly reduced, generally by 15%-30%. How to improve the toughness of concrete without significantly reducing the strength of concrete after adding polymers to concrete is a realistic problem before us.

[0003] Therefore, how to develop a hard-core soft-shell core-shell structure polymer and its concrete and preparation method is an urgent problem to be solved by technicians in this field. Summary of the invention

[0004] In view of this, the present invention provides a hard-core-soft-shell core-shell structure polymer and concrete thereof and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A hard-core-soft-shell core-shell structure polymer is prepared from the following raw materials in parts by weight: 200-240 parts of core monomer pre-emulsion, 160-200 parts of shell monomer pre-emulsion, 20 parts of initiator solution, and 4.8-6 parts of functional monomer;

[0007] The above core monomer pre-emulsion is prepared from the following raw materials in parts by weight:

[0008] Deionized water 100-120 parts, anionic emulsifier 3-3.36 parts, nonionic emulsifier 0.84-1 parts, nuclear monomer 100-120 parts;

[0009] The above-mentioned shell monomer pre-emulsion is prepared from the following raw materials in parts by weight:

[0010] 80-100 parts of deionized water, 2.24-3 parts of anionic emulsifier, 0.56-1 part of nonionic emulsifier, 80-100 parts of shell monomer;

[0011] The above initiator solution is prepared from the following raw materials in parts by weight:

[0012] 50 parts of deionized water, 4 parts of initiator.

[0013] Beneficial effects of the present invention: The hard-core-soft-shell core-shell structure polymer of the present invention can improve the toughness of concrete without reducing the strength of concrete after being added to concrete. The polymer of the present invention is a core-shell particle including a rigid core and a flexible shell layer, which is an effective way to achieve concrete toughening without reducing the strength of the concrete system.

[0014] Furthermore, the anionic emulsifier is sodium dodecyl sulfate, the nonionic emulsifier is polyethylene glycol octylphenyl ether, the core monomer is styrene, the shell monomer is butyl acrylate, the initiator is ammonium persulfate, and the functional monomer is acrylic acid.

[0015] The beneficial effects of adopting the above further technical solution are as follows: the core of the hard-core soft-shell core-shell structure polymer is made of hard monomer styrene, which gives the polymer a certain cohesive force, and the hard core provides strength support for concrete. The shell of the hard-core soft-shell core-shell structure polymer is made of soft monomer butyl acrylate, which gives the polymer a certain flexibility, and the soft shell provides higher toughness for concrete. Therefore, adding this hard-core soft-shell core-shell structure polymer to concrete can provide higher toughness for concrete without reducing the strength of concrete.

[0016] Sodium dodecyl sulfate, which contains a long hydrophilic head and a hydrophobic alkyl tail in its molecular structure, forms micelles in water and has good surface activity and emulsification properties. Polyethylene glycol octylphenyl ether, as a hydrophilic emulsifier, can make the emulsion stable and delicate, and can improve the smoothness and elasticity of the serous membrane. The combination of the two emulsifiers makes the prepared emulsion more stable.

[0017] Initiator is one of the important components in emulsion polymerization. The type of initiator directly affects the reaction rate, product properties and yield of emulsion polymerization. Ammonium persulfate is a thermal decomposition initiator with good water solubility. A small amount of it can initiate the polymerization reaction smoothly and generate a stable polymer.

[0018] The addition of functional monomer acrylic acid can give the polymer some special reaction properties such as hydrophilicity, weather resistance and cross-linking.

[0019] The present invention also provides a method for preparing a hard-core-soft-shell core-shell structure polymer, comprising the following steps:

[0020] (1) Weighing various raw materials according to the hard-core-soft-shell core-shell structure polymer described above;

[0021] (2) preparing a core monomer pre-emulsion: fully stirring and dissolving deionized water, anionic emulsifier and nonionic emulsifier, and then adding the core monomer and stirring to obtain a core monomer pre-emulsion;

[0022] (3) preparing a shell monomer pre-emulsion: fully stirring and dissolving deionized water, anionic emulsifier and nonionic emulsifier, and then adding the shell monomer and stirring to obtain a shell monomer pre-emulsion;

[0023] (4) preparing an initiator solution: thoroughly stirring and dissolving deionized water and an initiator to obtain an initiator solution;

[0024] (5) preparing a seed emulsion: dividing the obtained core monomer pre-emulsion into two parts, dividing the obtained initiator solution into three parts, heating the first part of the core monomer pre-emulsion, and then dropwise adding the first part of the initiator solution under stirring, and introducing nitrogen protection, and after the dropwise addition is completed, keeping the temperature until blue light appears, thereby obtaining a seed emulsion;

[0025] (6) Preparing the polymer core: the seed emulsion is kept warm, and the second part of the core monomer pre-emulsion and the second part of the initiator solution are added dropwise while stirring, and the temperature is kept warm after the addition is completed to obtain micro cross-linked particles of the polymer core;

[0026] (7) preparing a polymer shell: heating the obtained micro-crosslinked particles of the polymer core, and then adding the obtained shell monomer pre-emulsion, the third part of the initiator solution and the functional monomer dropwise while stirring, and keeping the temperature after the addition is completed to obtain a polymer emulsion;

[0027] (8) Adjusting the pH value of the polymer emulsion: The polymer emulsion is cooled naturally, and then ammonia water is added dropwise under stirring to adjust the pH value of the polymer emulsion to 7-8, and filtered to obtain a hard-core-soft-shell core-shell structure polymer.

[0028] Beneficial effects of the invention: The preparation method of the invention is simple, easy to operate, and suitable for wide production and application.

[0029] Further, the mass ratio of the first part of the core monomer pre-emulsion to the second part of the core monomer pre-emulsion is 20:(180-220);

[0030] The mass ratio of the first part of the initiator solution, the second part of the initiator solution and the third part of the initiator solution is 1:(9-11):(8-10).

[0031] Furthermore, in steps (2)-(3), a tissue homogenizer is used for stirring, the stirring speed is 8000-12000 r / min, the stirring time for adding the core monomer is 10 min, and the stirring time for adding the shell monomer is 10 min;

[0032] In steps (5)-(8), a mechanical stirrer is used for stirring at a stirring speed of 350 r / min;

[0033] In step (5), the dropping time is 30 min;

[0034] In steps (6)-(7), the dropping time is 2.5 h respectively.

[0035] The beneficial effect of adopting the above further technical solution is that obtaining a uniform and stable pre-emulsion is a prerequisite for the polymerization reaction, and in the preparation process of the pre-emulsion, the speed of stirring is a key factor. If the stirring rate is low, the pre-emulsion is easy to stratify and a uniform and stable pre-emulsion cannot be generated. A uniform and stable pre-emulsion can only be generated when the speed of the tissue homogenizer is 8000r / min-12000r / min.

[0036] Further, in step (5), the temperature of the first part of the core monomer pre-emulsion is raised to 70° C., and after the dropwise addition is completed, the temperature is kept for 30 minutes until blue light appears;

[0037] In step (6), the seed emulsion is continuously kept warm at 70° C. and kept warm for 1 hour after the dropwise addition is completed;

[0038] In step (7), the obtained micro-crosslinked particles of the polymer core are heated to 80° C. and kept warm for 1 hour after the dropwise addition is completed;

[0039] In step (8), the polymer emulsion is naturally cooled to 45°C.

[0040] The beneficial effect of adopting the above further technical solution: During the emulsion polymerization process, the temperature has a significant effect on the reaction rate. When the temperature is lower than 70°C, the reaction rate is significantly slowed down and the monomer cannot polymerize quickly. When the temperature is too high, exceeding 80°C, the emulsifier will precipitate from the solution, lose the emulsification effect, and the polymerization reaction cannot proceed normally.

[0041] The present invention also provides a hard-core soft-shell core-shell structure polymer concrete, comprising the following raw materials in parts by weight: 230-275 parts of cement, 135-180 parts of mineral admixtures, 635-705 parts of river sand, 1080-1125 parts of crushed stone, 18-50 parts of the hard-core soft-shell core-shell structure polymer, 4.0-6.5 parts of water reducer, and 130-144 parts of water.

[0042] The beneficial effects of the present invention are as follows: adding polymer emulsion to concrete improves the interface bonding between the mortar layer and the coarse aggregate in the concrete, and has a significant effect on improving the flexural strength of the concrete; and the hard core in the hard-core-soft-shell core-shell structure polymer provides strength support for the concrete, and the soft shell provides higher toughness for the concrete. Therefore, the hard-core-soft-shell core-shell structure polymer concrete prepared by the raw material components and dosage ratios defined by the present invention has higher toughness, and at the same time, the concrete strength is not reduced.

[0043] Further, the above-mentioned cement is P·O42.5 ordinary Portland cement;

[0044] The mineral admixture is one or both of fly ash and slag powder;

[0045] The fineness modulus of the above river sand is 2.3-3.0;

[0046] The particle gradation of the above-mentioned crushed stone is a continuous gradation of 5mm-25mm, 5mm-20mm or 5mm-10mm.

[0047] The water reducer is a polycarboxylate water reducer.

[0048] The beneficial effect of adopting the above further technical solution is: the combination of the above cement, mineral admixtures, river sand and crushed stone makes the concrete a tightly packed system, which is beneficial to the improvement of the mechanical properties of the concrete.

[0049] The present invention also provides a method for preparing a hard-core-soft-shell core-shell structure polymer concrete, comprising the following steps:

[0050] 1) Weighing various raw materials according to the hard-core-soft-shell core-shell polymer concrete mentioned above;

[0051] 2) mixing cement, mineral admixture, river sand and crushed stone to obtain a mixture;

[0052] 3) Add the obtained mixture to a hard-core-soft-shell core-shell structure polymer, a water reducer and water, stir and put it into a mold for hardening to obtain the hard-core-soft-shell core-shell structure polymer concrete.

[0053] Beneficial effects of the invention: The preparation method of the invention is simple, easy to operate, and suitable for wide production and application.

[0054] Further, in step 2), the stirring speed is 40-50 rpm and the stirring time is 20-30 s;

[0055] In step 3), the stirring speed is 40-50 rpm and the stirring time is 2-3 min.

[0056] The beneficial effect of adopting the above further technical solution is: through the stirring in step 2), all solids are mixed evenly, and through the stirring in step 3), all solids and liquids are mixed evenly to form a mixture in which each component is evenly dispersed. DETAILED DESCRIPTION

[0057] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0058] Example 1

[0059] The preparation method of hard-core soft-shell core-shell structure polymer concrete comprises the following steps:

[0060] (I) Preparation of hard-core soft-shell core-shell polymers

[0061] (1) Preparing a core monomer pre-emulsion: In a 500 mL round-bottom flask, 100 g of deionized water, 3 g of sodium dodecyl sulfate and 1 g of polyethylene glycol octylphenyl ether were fully stirred and dissolved, and then 100 g of styrene was added and stirred for 10 min using a tissue homogenizer at a stirring speed of 8000 r / min to obtain a core monomer pre-emulsion;

[0062] (2) preparing a shell monomer pre-emulsion: in a 500 mL round-bottom flask, 100 g of deionized water, 3 g of sodium dodecyl sulfate and 1 g of polyethylene glycol octylphenyl ether were fully stirred and dissolved, and then 100 g of butyl acrylate was added and stirred for 10 min using a tissue homogenizer at a stirring speed of 10,000 r / min to obtain a shell monomer pre-emulsion;

[0063] (3) preparing an initiator solution: in a 100 mL beaker, thoroughly stir and dissolve 50 g of deionized water and 4 g of ammonium persulfate to obtain an initiator solution;

[0064] (4) preparing a seed emulsion: the obtained core monomer pre-emulsion was divided into two parts, and the obtained initiator solution was divided into three parts. In a four-necked flask, 20 g of the core monomer pre-emulsion was heated to 70° C., and then stirred with a mechanical stirrer at a stirring speed of 350 r / min. In steps (5) to (8), the stirring speed was fixed, and 1 g of the initiator solution was added dropwise under stirring for 30 min. Nitrogen was introduced for protection. After the addition was completed, the mixture was kept warm for 30 min until blue light appeared, thereby obtaining a seed emulsion;

[0065] (5) Preparation of polymer core: In a four-necked flask, the seed emulsion was kept at 70° C., and 180 g of the core monomer pre-emulsion and 9 g of the initiator solution were added dropwise while stirring for 2.5 h. After the addition was completed, the mixture was kept at this temperature for 1 h to obtain micro-crosslinked particles of the polymer core;

[0066] (6) Preparation of polymer shell: In a four-necked flask, the obtained micro-crosslinked particles of the polymer core were heated to 80° C., and then 200 g of the obtained shell monomer pre-emulsion, 10 g of the initiator solution and 6 g of acrylic acid were added dropwise simultaneously under stirring for 2.5 h. After the addition was completed, the mixture was kept warm for 1 h to obtain a polymer emulsion;

[0067] (7) Adjusting the pH value of the polymer emulsion: The polymer emulsion was naturally cooled to 45°C, and then ammonia water was added dropwise under stirring to adjust the pH value of the polymer emulsion to 7-8, and filtered to obtain a hard-core-soft-shell core-shell structure polymer.

[0068] (II) Preparation of hard core soft shell core-shell polymer concrete

[0069] 1) Weigh 5.5kg of cement, 2.7kg of fly ash, 13.7kg of river sand, 22.5kg of crushed stone, 0.36kg of hard-core soft-shell core-shell structure polymer, 0.13kg of water reducer, and 2.88kg of water;

[0070] The cement is P·O42.5 ordinary Portland cement;

[0071] The fineness modulus of river sand is 2.3;

[0072] The particle gradation of crushed stone is 5mm-20mm continuous gradation.

[0073] The water reducer is a polycarboxylate water reducer, provided by Jiangsu Nigo Technology Co., Ltd., model JK-PCA.

[0074] 2) mixing cement, mineral admixture, river sand and crushed stone at a stirring speed of 47 rpm for 30 s to obtain a mixture;

[0075] 3) Add the obtained mixture to a hard-core soft-shell core-shell structure polymer, a water reducer and water, stir and put it into a mold to harden for 1 day, the stirring speed is 47 rpm, and the stirring time is 2 min to obtain a hard-core soft-shell core-shell structure polymer concrete.

[0076] The concrete without the hard-core soft-shell core-shell structure polymer of this example was used as comparative example 1 for testing. The slump of the concrete of comparative example 1 and example 1 was controlled to be 180 mm ± 20 mm, and the air content was 4.5% ± 0.5%. The concrete mix ratios of comparative example 1 and example 1 are shown in Table 1.

[0077] Table 1 Concrete mix ratio of comparative example 1 and embodiment 1 (kg)

[0078]

[0079] Example 2

[0080] The preparation method of hard-core soft-shell core-shell structure polymer concrete comprises the following steps:

[0081] (I) Preparation of hard-core soft-shell core-shell polymers

[0082] (1) Preparing a core monomer pre-emulsion: In a 500 mL round-bottom flask, 120 g of deionized water, 3.36 g of sodium dodecyl sulfate and 0.84 g of polyethylene glycol octylphenyl ether were fully stirred and dissolved, and then 120 g of styrene was added and stirred for 10 min using a tissue homogenizer at a stirring speed of 10,000 r / min to obtain a core monomer pre-emulsion;

[0083] (2) Preparing a shell monomer pre-emulsion: In a 500 mL round-bottom flask, 80 g of deionized water, 2.24 g of sodium dodecyl sulfate and 0.56 g of polyethylene glycol octylphenyl ether were fully stirred and dissolved, and then 80 g of butyl acrylate was added and stirred for 10 min using a tissue homogenizer at a stirring speed of 10,000 r / min to obtain a shell monomer pre-emulsion;

[0084] (3) preparing an initiator solution: in a 100 mL beaker, thoroughly stir and dissolve 50 g of deionized water and 4 g of ammonium persulfate to obtain an initiator solution;

[0085] (4) preparing a seed emulsion: the obtained core monomer pre-emulsion was divided into two parts, and the obtained initiator solution was divided into three parts. In a four-necked flask, 20 g of the core monomer pre-emulsion was heated to 70° C., and then stirred with a mechanical stirrer at a stirring speed of 350 r / min. In steps (5) to (8), the stirring speed was fixed, and 1 g of the initiator solution was added dropwise under stirring for 30 min. Nitrogen was introduced for protection. After the addition was completed, the mixture was kept warm for 30 min until blue light appeared, thereby obtaining a seed emulsion;

[0086] (5) Preparation of polymer core: In a four-necked flask, the seed emulsion was kept at 70° C., and 220 g of the core monomer pre-emulsion and 11 g of the second part of the initiator solution were added dropwise while stirring for 2.5 h. After the addition was completed, the mixture was kept at this temperature for 1 h to obtain micro-crosslinked particles of the polymer core;

[0087] (6) Preparation of polymer shell: In a four-necked flask, the obtained micro-crosslinked particles of the polymer core were heated to 80° C., and then 160 g of the obtained shell monomer pre-emulsion, 8 g of the initiator solution and 4.8 g of acrylic acid were added dropwise simultaneously under stirring for 2.5 h. After the addition was completed, the mixture was kept warm for 1 h to obtain a polymer emulsion;

[0088] (7) Adjusting the pH value of the polymer emulsion: The polymer emulsion was naturally cooled to 45°C, and then ammonia water was added dropwise under stirring to adjust the pH value of the polymer emulsion to 7-8, and filtered to obtain a hard-core-soft-shell core-shell structure polymer.

[0089] (II) Preparation of hard core soft shell core-shell polymer concrete

[0090] 1) Weigh 5.04kg cement, 3.36kg fly ash, 14.1kg river sand, 22kg crushed stone, 0.68kg hard-core soft-shell core-shell structure polymer, 0.08kg water reducer, and 2.8kg water;

[0091] The cement is P·O42.5 ordinary Portland cement;

[0092] The fineness modulus of river sand is 2.7;

[0093] The particle gradation of crushed stone is 5mm-10mm continuous gradation.

[0094] The water reducer is a polycarboxylate water reducer, provided by Jiangsu Nigo Technology Co., Ltd., model JK-PCA.

[0095] 2) mixing cement, mineral admixture, river sand and crushed stone at a stirring speed of 45 rpm for 30 s to obtain a mixture;

[0096] 3) Add the obtained mixture to a hard-core soft-shell core-shell structure polymer, a water reducer and water, stir and put it into a mold to harden for 1 day, the stirring speed is 45 rpm, the stirring time is 2 min, and a hard-core soft-shell core-shell structure polymer concrete is obtained.

[0097] The concrete without the core-shell structure polymer of this example was used as comparative example 2 for testing. The slump of the concrete of comparative example 2 and example 2 was controlled to be 180 mm ± 20 mm, and the air content was 4.5% ± 0.5%. The concrete mix ratios of comparative example 2 and example 2 are shown in Table 2.

[0098] Table 2 Concrete mix ratio of comparative example 2 and embodiment 2 (kg)

[0099]

[0100]

[0101] Example 3

[0102] The preparation method of hard-core soft-shell core-shell structure polymer concrete comprises the following steps:

[0103] (I) Preparation of hard-core soft-shell core-shell polymers

[0104] (1) Preparing a core monomer pre-emulsion: In a 500 mL round-bottom flask, 120 g of deionized water, 3.36 g of sodium dodecyl sulfate and 0.84 g of polyethylene glycol octylphenyl ether were fully stirred and dissolved, and then 120 g of styrene was added and stirred for 10 min using a tissue homogenizer at a stirring speed of 12000 r / min to obtain a core monomer pre-emulsion;

[0105] (2) Preparing a shell monomer pre-emulsion: In a 500 mL round-bottom flask, 80 g of deionized water, 2.24 g of sodium dodecyl sulfate and 0.56 g of polyethylene glycol octylphenyl ether were fully stirred and dissolved, and then 80 g of butyl acrylate was added and stirred for 10 min using a tissue homogenizer at a stirring speed of 12000 r / min to obtain a shell monomer pre-emulsion;

[0106] (3) preparing an initiator solution: in a 100 mL beaker, thoroughly stir and dissolve 50 g of deionized water and 4 g of ammonium persulfate to obtain an initiator solution;

[0107] (4) preparing a seed emulsion: the obtained core monomer pre-emulsion was divided into two parts, and the obtained initiator solution was divided into three parts. In a four-necked flask, 20 g of the core monomer pre-emulsion was heated to 70° C., and then stirred with a mechanical stirrer at a stirring speed of 350 r / min. In steps (5) to (8), the stirring speed was fixed, and 1 g of the initiator solution was added dropwise under stirring for 30 min. Nitrogen was introduced for protection. After the addition was completed, the mixture was kept warm for 30 min until blue light appeared, thereby obtaining a seed emulsion;

[0108] (5) Preparation of polymer core: In a four-necked flask, the seed emulsion was kept warm at 70°C, and 220 g of the core monomer pre-emulsion and 11 g of the initiator solution were added dropwise while stirring for 2.5 h. After the addition was completed, the mixture was kept warm for 1 h to obtain micro-crosslinked particles of the polymer core;

[0109] (6) Preparation of polymer shell: In a four-necked flask, the obtained micro-crosslinked particles of the polymer core were heated to 80° C., and then 160 g of the obtained shell monomer pre-emulsion, 8 g of the third part of the initiator solution and 4.8 g of acrylic acid were added dropwise at the same time under stirring for 2.5 h. After the addition was completed, the mixture was kept warm for 1 h to obtain a polymer emulsion;

[0110] (7) Adjusting the pH value of the polymer emulsion: The polymer emulsion was naturally cooled to 45°C, and then ammonia water was added dropwise under stirring to adjust the pH value of the polymer emulsion to 7-8, and filtered to obtain a hard-core-soft-shell core-shell structure polymer.

[0111] (II) Preparation of hard-core soft-shell core-shell polymer concrete

[0112] 1) Weigh 4.6kg cement, 3.6kg slag powder, 12.7kg river sand, 21.6kg crushed stone, 1kg hard-core soft-shell core-shell structure polymer, 0.1kg water reducer, and 2.6kg water;

[0113] The cement is P·O42.5 ordinary Portland cement;

[0114] The fineness modulus of river sand is 3.0;

[0115] The particle gradation of crushed stone is 5mm-25mm continuous gradation.

[0116] The water reducer is a polycarboxylate water reducer, provided by Jiangsu Nigo Technology Co., Ltd., model JK-PCA.

[0117] 2) mixing cement, mineral admixture, river sand and crushed stone at a stirring speed of 47 rpm for 30 s to obtain a mixture;

[0118] 3) Add the obtained mixture to a hard-core soft-shell core-shell structure polymer, a water reducer and water, stir and put it into a mold to harden for 1 day, the stirring speed is 47 rpm, and the stirring time is 2 min to obtain a hard-core soft-shell core-shell structure polymer concrete.

[0119] The concrete without the core-shell structure polymer of this example was used as comparative example 3 for testing. The slump of the concrete of comparative example 3 and example 3 was controlled to be 180 mm ± 20 mm, and the air content was 4.5% ± 0.5%. The concrete mix ratios of comparative example 3 and example 3 are shown in Table 3.

[0120] Table 3 Concrete mix ratio of comparative example 3 and embodiment 3 (kg)

[0121]

[0122] Effect verification

[0123] The relevant properties of the hard-core soft-shell core-shell structure polymer in each example were tested, including PDI (polymer dispersibility index), Zeta potential, solid content, conversion rate and pH value. The results are shown in Table 4.

[0124] Table 4 Properties of hard core soft shell core-shell structure polymers

[0125]

[0126] The concrete related performance tests of each embodiment were tested. Among them, the compressive strength and flexural strength of concrete were carried out in accordance with GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the toughness of concrete was characterized by the fold-to-compression ratio (ratio of flexural strength to compressive strength). The compressive strength and flexural strength of Examples 1-3 and Comparative Examples 1-3 were tested at 3d and 28d ages, and the fold-to-compression ratio and toughness improvement rate were calculated, where the toughness improvement rate is the improvement rate of the fold-to-compression ratio of the embodiment relative to the fold-to-compression ratio of the comparative example. The specific test results are shown in Table 5.

[0127] Table 5

[0128]

[0129] As can be seen from Table 5, the compressive strength of Examples 1-3 is not reduced relative to Comparative Examples 1-3. Regardless of the 3d age or 28d age, the toughness improvement rate of Examples 1-3 is above 20%. Specifically, the toughness improvement rates of Examples 1-3 at the 3d age are 20%, 25% and 26%, respectively, and the toughness improvement rates of Examples 1-3 at the 28d age are 24%, 27% and 33%, respectively.

[0130] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A hard-core soft-shell core-shell structure polymer, characterized in that: It is prepared from the following raw materials in parts by weight: 200-240 parts of core monomer pre-emulsion, 160-200 parts of shell monomer pre-emulsion, 20 parts of initiator solution, and 4.8-6 parts of functional monomer; The core monomer pre-emulsion is prepared from the following raw materials in parts by weight: Deionized water 100-120 parts, anionic emulsifier 3-3.36 parts, nonionic emulsifier 0.84-1 parts, nuclear monomer 100-120 parts; The shell monomer pre-emulsion is prepared from the following raw materials in parts by weight: 80-100 parts of deionized water, 2.24-3 parts of anionic emulsifier, 0.56-1 part of nonionic emulsifier, 80-100 parts of shell monomer; The initiator solution is prepared from the following raw materials in parts by weight: 50 parts of deionized water, 4 parts of initiator.

2. A hard-core-soft-shell core-shell structure polymer according to claim 1, characterized in that: The anionic emulsifier is sodium dodecyl sulfonate, the nonionic emulsifier is polyethylene glycol octyl phenyl ether, the core monomer is styrene, the shell monomer is butyl acrylate, the initiator is ammonium persulfate, and the functional monomer is acrylic acid.

3. A method for preparing a hard-core soft-shell core-shell structure polymer, characterized in that: The steps include: (1) Weighing the raw materials according to the hard-core-soft-shell core-shell structure polymer of claim 1 or 2; (2) preparing a core monomer pre-emulsion: fully stirring and dissolving deionized water, anionic emulsifier and nonionic emulsifier, and then adding the core monomer and stirring to obtain a core monomer pre-emulsion; (3) preparing a shell monomer pre-emulsion: fully stirring and dissolving deionized water, anionic emulsifier and nonionic emulsifier, and then adding the shell monomer and stirring to obtain a shell monomer pre-emulsion; (4) preparing an initiator solution: thoroughly stirring and dissolving deionized water and an initiator to obtain an initiator solution; (5) preparing a seed emulsion: dividing the obtained core monomer pre-emulsion into two parts, dividing the obtained initiator solution into three parts, heating the first part of the core monomer pre-emulsion, and then dropwise adding the first part of the initiator solution under stirring, and introducing nitrogen protection, and after the dropwise addition is completed, keeping the temperature until blue light appears, thereby obtaining a seed emulsion; (6) Preparing the polymer core: the seed emulsion is kept warm, and the second part of the core monomer pre-emulsion and the second part of the initiator solution are added dropwise while stirring, and the temperature is kept warm after the addition is completed to obtain micro cross-linked particles of the polymer core; (7) preparing a polymer shell: heating the obtained micro-crosslinked particles of the polymer core, and then adding the obtained shell monomer pre-emulsion, the third part of the initiator solution and the functional monomer dropwise while stirring, and keeping the temperature after the addition is completed to obtain a polymer emulsion; (8) Adjusting the pH value of the polymer emulsion: The polymer emulsion is cooled naturally, and then ammonia water is added dropwise under stirring to adjust the pH value of the polymer emulsion to 7-8, and filtered to obtain a hard-core-soft-shell core-shell structure polymer.

4. The method for preparing a hard-core-soft-shell core-shell structure polymer according to claim 3, characterized in that: The mass ratio of the first part of the core monomer pre-emulsion to the second part of the core monomer pre-emulsion is 20:(180-220); The mass ratio of the first part of the initiator solution, the second part of the initiator solution and the third part of the initiator solution is 1:(9-11):(8-10).

5. The method for preparing a hard-core-soft-shell core-shell structure polymer according to claim 3, characterized in that: In steps (2)-(3), a tissue homogenizer is used for stirring at a speed of 8000-12000 r / min, the stirring time for adding the core monomer is 10 min, and the stirring time for adding the shell monomer is 10 min; In steps (5)-(8), a mechanical stirrer is used for stirring at a stirring speed of 350 r / min; In step (5), the dropping time is 30 min; In steps (6)-(7), the dropping time is 2.5 h respectively.

6. The method for preparing a hard-core-soft-shell core-shell structure polymer according to claim 3, characterized in that: In step (5), the temperature of the first part of the core monomer pre-emulsion is raised to 70° C. After the dropwise addition is completed, the temperature is kept for 30 minutes until blue light appears; In step (6), the seed emulsion is continuously kept warm at 70° C. and kept warm for 1 hour after the dropwise addition is completed; In step (7), the obtained micro-crosslinked particles of the polymer core are heated to 80° C. and kept warm for 1 hour after the dropwise addition is completed; In step (8), the polymer emulsion is naturally cooled to 45°C.

7. A hard-core-soft-shell core-shell polymer concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 230-275 parts of cement, 135-180 parts of mineral admixtures, 635-705 parts of river sand, 1080-1125 parts of crushed stone, 18-50 parts of the hard-core-soft-shell core-shell structure polymer according to claim 1 or 2, 4.0-6.5 parts of water reducer and 130-144 parts of water.

8. The hard-core-soft-shell core-shell polymer concrete according to claim 7, characterized in that: The cement is P·O42.5 ordinary Portland cement; The mineral admixture is one or both of fly ash and slag powder; The fineness modulus of the river sand is 2.3-3.0; The particle gradation of the crushed stone is a continuous gradation of 5mm-25mm, 5mm-20mm or 5mm-10mm. The water reducer is a polycarboxylate water reducer.

9. A method for preparing a hard-core-soft-shell core-shell polymer concrete, characterized in that: The following steps are involved: 1) Weighing the raw materials according to the hard-core-soft-shell core-shell polymer concrete of claim 7 or 8; 2) mixing cement, mineral admixture, river sand and crushed stone to obtain a mixture; 3) adding the obtained mixture to a hard-core-soft-shell core-shell structure polymer, a water reducing agent and water, stirring and then putting the mixture into a mold for hardening to obtain the hard-core-soft-shell core-shell structure polymer concrete.

10. The method for preparing a hard-core-soft-shell core-shell polymer concrete according to claim 9, characterized in that: In step 2), the stirring speed is 40-50 rpm and the stirring time is 20-30 s; In step 3), the stirring speed is 40-50 rpm and the stirring time is 2-3 min.

Citation Information

Patent Citations

  • Preparation method of re-dispersible latex powder of acrylic acid

    CN101575399A

  • Preparation method of polyacrylic acid latex for modified concrete of road

    CN102718922A

  • Polymer / clay nanometer composite material of core-shell structure and preparing method thereof

    CN105111606A

  • Preparation method of benzene ring core-shell emulsion polymer for cement

    CN110606918A

  • Core-shell structure polymer cement modifier, preparation method and cement-based material

    CN111777717A